PENGARUH PEMBERIAN EKSTRAK DAUN KELOR TERHADAP KADAR GULA DARAH PADA LANSIA PUTRI DI KLATEN - Rohmawati, Wiwin; Uswatun Qoyyimah, Anna; Wahyuni, Sri; Dynamurti Wintoro, Piscolia; Sawitri, Endang (INVOLUSI: Jurnal Ilmu Kebidanan, 2024)
Some of the changes that occur in the elderly, one of which is changes in the endocrine system that occurs in the elderly, namely increasing blood sugar levels, if left unchecked, will cause diabetes mellitus. Non- Communicable Diseases (NCDs), including Diabetes, have now become a serious threat to global health. The significant increase in the prevalence of diabetes carries the risk of developing other diseases, such as heart attacks, strokes, blindness and kidney failure and can even cause paralysis and death. Non-pharmacological techniques are additional therapy besides consuming drugs, namely by consuming Moringa oleifera extract. Moringa leaves contain antioxidants such as flavonoids, vitamin A, vitamin E, vitamin C and also contain selenium which helps lower blood glucose levels. This study aims to determine whether there is an effect between Moringa leaf extract on the blood sugar levels of elderly women in Kalikebo Trucuk, Klaten. Quasi-experimental research method, Pre-Experimental Design (Non Design) research design with pre test- post test with control group, the sample in this study was 30 respondents who were divided into 2 groups, namely 15 respondents in the case group who were given Moringa leaf extract for 7 day 2x1 500 (mg/day) and 15 respondents in the control group, this study used the Paired Samples T Test with a p value of 0.000 < 0.05. This shows that there is an effect of giving Moringa leaf extract on blood sugar levels in elderly women in Kalikebo Trucuk, Klaten. The conclusion of the research is that there is an effect of giving Moringa oleifera extract on blood sugar levels in elderly women. Respondents suggested checking blood sugar more regularly and consuming Moringa oleifera extract to lower blood sugar levels